2018
DOI: 10.3390/met8070487
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Fractographic Analysis of Plastically Deformed Al-Zn-Mg Alloy Subjected to Combined High-Cycle Bending-Torsion Fatigue

Abstract: Abstract:The present manuscript aims to determine the effect of various deformation levels during low-temperature thermo-mechanical treatment (LTTT) on the microstructure and fatigue strength of Zr-microalloyed Al-Zn-Mg alloy. The fatigue strength of the alloy was studied in high-cycle bending-torsion tests. The determination of the influence of plastic deformation level during LTTT on the microstructure was based on transmission electron microscopy (TEM) observations. The analysis of fracture after the fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It should be noted that a of the first band of the beach marks was 1.5~2.5 mm and not accurate enough to track the very early crack initiation, for which further investigations were still needed. Moreover, the question of how steel grades and yield strengths influence the fatigue strength remains to be answered through microstructural and fractographic analysis [ 25 ].…”
Section: Test Resultsmentioning
confidence: 99%
“…It should be noted that a of the first band of the beach marks was 1.5~2.5 mm and not accurate enough to track the very early crack initiation, for which further investigations were still needed. Moreover, the question of how steel grades and yield strengths influence the fatigue strength remains to be answered through microstructural and fractographic analysis [ 25 ].…”
Section: Test Resultsmentioning
confidence: 99%
“…In the case of the 7003 alloy, the material for the tests was an industrial aluminium alloy of Al-Zn-Mg type in the form of a sheet with dimensions 400 × 200 × 20 mm [ 34 , 35 , 36 ]. Al-Zn-Mg alloys of the 7000 series show the highest strength potential among alloys for precipitation hardening.…”
Section: Methodsmentioning
confidence: 99%
“…The aluminium alloy group analyzed consists of six materials: 6082-T6 [ 31 ], 2017A-T4 [ 32 ], D-30 [ 33 ], and three types of Al-Zn-Mg type alloys in grade 7003 for plastic working after the low-temperature heat-plastic treatment [ 34 , 35 , 36 ]. The results were used to analyze the correctness of the proposed model of fatigue life estimation.…”
Section: Introductionmentioning
confidence: 99%
“…In [24][25], a fractographic analysis of fatigue fractures of aluminum alloys after cyclic bending and torsion tests was carried out. As a result, it was found that crack propagation occurs mainly by connecting successive cracks that are formed at adjacent grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…In [34], the effect of strain location on pitting corrosion of aluminum alloys [20,[24][25]32]. An analysis of the influence of various treatment methods on the fatigue limit of magnesium alloy [27] can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%